The Teacher Problems in Implementing the Independent Curriculum in Islamic Religious Education Subjects - Sylva Rahmah Hafiz; Abdul Fattah Nasution; Widia Rahayu; Muliadi; Cahaya Maharani Sitompul (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This article explores the challenges faced by teachers in implementing the